Dealer financial conditions and lender-of-last-resort facilities - Viral V. Acharya; Michael J. Fleming; Warren B. Hrung; Asani Sarkar (Federal Reserve Bank of New York, 2014)
We examine the financial conditions of dealers that participated in two of the Federal Reserve's lender-of-last-resort (LOLR) facilities - the Term Securities Lending Facility (TSLF) and the Primary Dealer Credit Facility (PDCF) - that provided liquidity against a range of assets during 2008-09. Dealers with lower equity returns and greater leverage prior to borrowing from the facilities were more likely to participate in the programs, borrow more, and - in the case of the TSLF - at higher bidding rates. Dealers with less liquid collateral on their balance sheets before the facilities were introduced also tended to borrow more. There also appear to be some interaction effects between financial performance and balance sheet liquidity in explaining dealer behavior. The results suggest that both financial performance and balance sheet liquidity play a role in LOLR utilization.
Keywords: G01; G28; E58; D44; 330; lender of last resort; central banking; crises; illiquidity; insolvency; stigma